Effect of adrenergic agonists on coronary blood flow: a laboratory study in healthy volunteers. Issue 10 (24th May 2016) - Vargas Pelaez, Alvaro F.; Gao, Zhaohui; Ahmad, Tariq A.; Leuenberger, Urs A.; Proctor, David N.; Maman, Stephan R.; Muller, Matthew D.
Abstract: Myocardial oxygen supply and demand mismatch is fundamental to the pathophysiology of ischemia and infarction. The sympathetic nervous system, through α ‐adrenergic receptors and β ‐adrenergic receptors, influences both myocardial oxygen supply and demand. In animal models, mechanistic studies have established that adrenergic receptors contribute to coronary vascular tone. The purpose of this laboratory study was to noninvasively quantify coronary responses to adrenergic receptor stimulation in humans. Fourteen healthy volunteers (11 men and 3 women) performed isometric handgrip exercise to fatigue followed by intravenous infusion of isoproterenol. A subset of individuals also received infusions of phenylephrine ( n = 6), terbutaline ( n = 10), and epinephrine ( n = 4); all dosages were based on fat‐free mass and were infused slowly to achieve steady‐state. The left anterior descending coronary artery was visualized using Doppler echocardiography. Beat‐by‐beat heart rate (HR), blood pressure (BP), peak diastolic coronary velocity (CBVpeak), and coronary velocity time integral were calculated. Data are presented as M ± SD. Isometric handgrip elicited significant increases in BP, HR, and CBVpeak (from 23.3 ± 5.3 to 34.5 ± 9.9 cm/sec). Isoproterenol raised HR and CBVpeak (from 22.6 ± 4.8 to 43.9 ± 12.4 cm/sec). Terbutaline and epinephrine evoked coronary hyperemia whereas phenylephrine did not significantly alter CBVpeak. Different indices of coronary hyperemia (changes in CBVpeak and velocity time integral) were significantly correlated ( R = 0.803). The current data indicate that coronary hyperemia occurs in healthy humans in response to isometric handgrip exercise and low‐dose, steady‐state infusions of isoproterenol, terbutaline, and epinephrine. The contribution of β 1 versus β 2 receptors to coronary hyperemia remains to be determined. In this echocardiographic study, we demonstrate that coronary blood flow increases when β ‐adrenergic receptors are stimulated (i.e., during exercise and different intravenous infusions). Our infusion paradigms and beat‐by‐beat imaging methodologies can be used in future studies to evaluate age‐, sex‐, and disease‐ differences in adrenergic control of coronary blood flow. Abstract : In this echocardiographic study, we demonstrate that coronary blood flow increases when β ‐adrenergic receptors are stimulated (i.e., during exercise and different intravenous infusions). Our infusion paradigms and beat‐by‐beat imaging methodologies can be used in future studies to evaluate age‐, sex‐, and disease‐differences in adrenergic control of coronary blood flow.